Investigation of the effects of Pseudomonas aeruginosa cell signalling on host-pathogen interactions during infection - Yam, Joey Kuok Hoong (Nanyang Technological University, 2017)
Bacterial biofilms are highly tolerant to harsh conditions including antimicrobial agents and host immunity. Biofilms have been associated with chronic and persistent infections, which is a severe threat to the public health. Hence, there is an urgent need to develop treatments to eradicate these biofilms during infections. Treatment with colistin, one of the “last-resort” antibiotics, to Pseudomonas aeruginosa biofilm leads to the development of colistin-tolerant subpopulations. In the first study, we determined the mechanism of the development of P. aeruginosa colistin-tolerant subpopulations in biofilm in dynamic flow cell system via pulsed-SILAC proteomics-approached and showed that quorum sensing (QS) is important during the colistin-tolerant subpopulation development process. In the second study, P. aeruginosa is observed to form cell aggregates on cornea during infection, but the physiology of the cell aggregates remain unknown. Here, we proved that cyclic-di-GMP signaling plays a key role in biofilm formation on the wounded mouse cornea. Regulating the intracellular cyclic-di-GMP content affects the infection outcome. Finally, we designed two new treatment strategies by manipulating QS or cyclicdi-GMP signaling in the biofilm, in conjunction with colistin treatment and showed the feasibility of these treatment strategies in both in vitro and in vivo models.